Electrical Injuries in Animals: Causes, Pathogenesis, and Morphological Findings. (September 2016) - Schulze, C.; Peters, M.; Baumgärtner, W.; Wohlsein, P.
Electrical injuries in animals occur most often accidentally. They comprise contact to various forms of currents, including alternating, rotary, or direct currents. Depending on various parameters of the current (including the type of circuit, voltage, current and duration of exposure) and conditions of the animal (such as wet or dry hair coat and pathway of current through the body), lesions may be absent or may include early or localized development of rigor mortis, signs of acute circulatory failure, or severe thermoelectrical burns. Such burns may present as external current marks, singed hair or feathers, metallization of the skin, or occasionally internal electroporation injury resulting in muscle necrosis, hemolysis, vascular damage with thrombosis, injury to brain and spinal cord, or skeletal fractures. Furthermore, lightning strikes occur regularly in grazing animals, which have greater risk of death from step potentials (ground current) in addition to direct strike and contact injury. Such cases may have no lesions, external signs of linear or punctate burns, keraunographic markings, or exit burns on the soles of the hooves or the coronary bands. Besides detailed information about the circumstances at the location where the animal was found, electrical injuries in animals require a thorough morphological workup, including additional investigations in conjunction with certain knowledge about the possible lesion spectrum.